Transformasi sepatu boots kulit vintage menuju boots kulit yang lebih ergonomis - Febriantoro, Raihan; Herdiana, Wyna; Tiffany, Florentina (Institut Seni Indonesia Yogyakarta, 2025)
Leather boots have long been a top choice in the world of fashion and functionality, offering durability and classic style. The latest innovation brings the transformation of traditional leather boots into ergonomic leather boots, designed to improve comfort and support the normal functional movement anatomy of the foot. This shoe combines premium leather materials with ergonomic technology, such as a soft sole, adjustable arch support, and flexible design to support the natural movement of the foot, so that boot users avoid the risk of minor injury due to the use of boots with leather materials. With a focus on foot health and long-term wearing comfort, these ergonomic leather boots not only maintain the classic aesthetic but also present additional benefits to the user's daily life, whether for light activities or heavy work. This transformation paved the way for products that integrate style with function health, making it an ideal choice for modern consumers who prioritize comfort without sacrificing appearance. The results of the study show that users of leather boots often experience minor injuries such as blistered feet, impaired blood circulation, and difficulty moving the legs freely according to their normal function. The factors that affect this are because the shoe does not have poor air circulation, the material is less flexible, and the arrangement of components that do not pay attention to the ergonomics of the foot. Users love boots that can be worn both for outdoor and daily needs.